Evaluation of Suitable Intercrops for Jatropha curcas based Agroforestry Systems - Divya, M.P.; Santhi, R.; Ramesh, K.R. (Indian Journal of Agroforestry, 2020)
With an objective of finding out the suitable intercrops for Jatropha based agroforestry system, an experiment was conducted with Jatropha and seven agricultural crops as intercrops. The results showed that the plant height and grain yield of the intercrops were reduced under Jatropha trees of different spacing when compared to pure crops. Among the different spacing, maximum reduction in growth and yield of the intercrops was observed at closer spacing (2mx2m) of Jatropha and minimum reduction at wider spacing (4mx3m). The magnitude of reduction in the intercrop yield decreased with the increase of spacing. Among the seven intercrops, significantly maximum reduction in plant height and grain yield was recorded in french bean and soybean during first and second intercropping respectively and minimum reduction was observed in cowpea at both intercropping under different spacing of Jatropha. From the study, it is concluded that cowpea followed by groundnut are the suitable crops for Jatropha based agroforestry system at the tree spacing of either 4mx2m or 4mx3m.